Product Development of Boran Rice Using the Value Engineering Method - M Fahkry; Alfirmansyah, Ahmad; Hidayat, Khoirul (Universitas Muhammadiyah Sidoarjo, 2022)
Boran rice is a typical food from Lamongan Regency. The hallmark of boran rice lies in its different seasonings from other cooking spices. Boran seasoning can only be found in Lamongan Regency at this time, and the method of presentation is still simple, so further product development is necessary. This study aims to determine the most critical factors and the best alternative in developing boran rice products. The method used is the Value Engineering (VE) method. Applying the Value Engineering method can help develop products with high value and low costs without compromising product quality and reliability. This study indicates that boran seasoning products have four most important factors: the level of spiciness, packaging, net weight, and viscosity. The chosen alternative with the highest value is the 1st alternative at IDR 9.349 and the value 1.106. Alternative 1 with the criteria for level 1 spiciness, PET plastic bottle packaging, net weight 250 grams with a thick viscosity level. The results of the added value analysis compared to competing products, namely boran seasoning on the market, get an added value of Rp. 4,349/package, the added value ratio is 86.98%, and the profit ratio is 46.52%.